Petrographic observations and phase properties for sample sets from Wadi Somerah (OM10-Sam) and Wadi Wariyah (OM10-War), Oman - Dominik Mock; David Axford Neave; Samuel Müller; Dieter Garbe-Schönberg; Olivier Namur; Benoit Ildefonse; Jürgen Koepke (PANGAEA, 2020)
As largest and best-exposed paleo-fast-spread oceanic crust on land, the Samail ophiolite in the Sultanate of Oman represents an ideal natural laboratory for investigating processes at fast-spreading mid-ocean ridges. We studied two layered gabbro sequences from different stratigraphic depths: one from the middle of the plutonic crust showing dm-scale modal layering with olivine abundance gradually decreasing from layer base to top (Wadi Somerah, Sumail block) and one located near the crust-mantle boundary showing mm-scale layers being enriched in olivine (Wadi Wariyah, Wadi Tayin block). Petrographic analyses were performed at the Institut für Mineralogie (Leibniz Universität Hannover, Germany) for thin-section description. Plagioclase and Clinopyroxene are present in all samples, most of the samples also include olivine as primary phase and are therefore described as olivine gabbro. The olivine content increases per layer towards the layer base. Grain sizes of the three primary phases olivine, plagioclase and clinopyroxene vary between 0.2 and 5 mm. Olivine usually forms the largest grains, plagioclase the smallest ones. The grain shapes are generally subhedral, their habit is prismatic or, occasionally, irregular or elongated. Some olivine grains show reaction rims or contain plagioclase chadacrysts. Poikilitic clinopyroxene also containing plagioclase as chadacrysts is very common. The described phases are only the primary minerals not taking the low to medium degree of alteration and therefore presence of secondary phases into account.